2022
DOI: 10.3389/fonc.2022.940314
|View full text |Cite
|
Sign up to set email alerts
|

Potential utility of miRNAs for liquid biopsy in breast cancer

Abstract: Breast cancer (BC) remains the most prevalent malignancy due to its incidence rate, recurrence, and metastasis in women. Conventional strategies of cancer detection– mammography and tissue biopsy lack the capacity to detect the complete cancer genomic landscape. Besides, they often give false- positive or negative results. The presence of this and other disadvantages such as invasiveness, high-cost, and side effects necessitates developing new strategies to overcome the BC burden. Liquid biopsy (LB) has been b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 215 publications
0
5
0
2
Order By: Relevance
“…Los miARN son pequeñas moléculas de ARN que regulan la expresión génica y están involucrados en la carcinogénesis (13). La dete cción de miARNs específicos en la sangre de pacientes con CM mediante BL puede servir como biomarcadores para la detección temprana, el pronóstico y la respuesta al tratamiento (14).…”
Section: Microarn (Miarn)unclassified
“…Los miARN son pequeñas moléculas de ARN que regulan la expresión génica y están involucrados en la carcinogénesis (13). La dete cción de miARNs específicos en la sangre de pacientes con CM mediante BL puede servir como biomarcadores para la detección temprana, el pronóstico y la respuesta al tratamiento (14).…”
Section: Microarn (Miarn)unclassified
“…A recent study analyzing total levels of circulating cf-miRNA demonstrated that high plasma levels of cf-miRNA were significantly associated with unfavorable clinical features, including tumor stage, tumor load and the presence of metastasis at diagnosis [ 274 ]. Various circulating miRNAs have been suggested to be potential biomarkers for BC prognosis [ 275 ]. Among them, levels of exosomal miR-148a were recently reported to be considerably lower in BC patients and low levels were associated with a poor clinical outcome in BC patients, suggesting this miRNA to be a potential prognostic biomarker [ 276 ].…”
Section: The Role Of Ncrnas In Diagnosis Prognosis and Prediction Or ...mentioning
confidence: 99%
“…In contrast, various studies analyzed intratumoral ncRNA expression in BC tissue and their implication for the ET response [ 279 ]. Today, analysis of circulating ncRNAs in liquid biopsies is considered to be a better and less invasive method [ 275 , 277 ], and initial studies exist that provide proof-of-concept [ 280 ]. Exosomal miR-221/222 were the first miRNAs shown to confer resistance to tamoxifen and fulvestrant in BC cells via downregulation of Erα [ 125 , 128 ].…”
Section: The Role Of Ncrnas In Diagnosis Prognosis and Prediction Or ...mentioning
confidence: 99%
“…Ginsenoside Rg2 Ginsenoside Rg2 has the functions of enhancing memory, improving metabolism, protecting heart, as well as anti-cancer ( Liu X et al, 2022 ). It is reported that ginsenoside Rg2 induces cell cycle arrest, inhibits proliferation and drives apoptosis of BC cells ( Jeon et al, 2021a ).…”
Section: Anti-breast Cancer Activity Of Ginsenosidesmentioning
confidence: 99%